Fios e furos: a trama da subjetividade e a educação - Mériti de Souza (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
Discusses the constitution of subjectivity cut through with pathos and logos and addressed to the singular and the collective. This conception requires the analysis of that which is excluded from the individualised identity of modern man and of knowledge as anchored exclusively in reason. Based on research developed with the school population and on listening to speeches produced by these people situated in subjective places with relation to knowledge, we question the possibility of pedagogical practice constituting experience, which produces subjective effects.